2017
DOI: 10.4103/0972-3919.198471
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally detected agenesis of dorsal pancreas on pet/ct: Case report and review of literature

Abstract: Agenesis of Dorsal Pancreas (ADP) is a rare congenital anomaly characterized by the absence of body and tail of pancreas. We report a case of incidentally detected ADP on Contrast Enhanced Computed Tomography (CECT) component of Fluorodeoxyglucose Positron Emission Tomography (FDG PET/CT) in a treated case of carcinoma (Ca) tongue with suspected local recurrence. Dependent Intestine Sign, hallmark of ADP on CECT imaging was noted in our patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…With the development of medical imaging technology, many ways to diagnose agenesis of the dorsal pancreas have been established, such as CT, magnetic resonance imaging, ultrasound, and EUS. Kabnurkar et al 9 recently reported that features of agenesis of the dorsal pancreas features as shown by positron emission tomography/CT, ERCP, or MRCP are necessary to reveal the major and accessory duct systems. 10 Differential diagnoses of agenesis of the dorsal pancreas include pancreas divisum and pseudo-agenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of medical imaging technology, many ways to diagnose agenesis of the dorsal pancreas have been established, such as CT, magnetic resonance imaging, ultrasound, and EUS. Kabnurkar et al 9 recently reported that features of agenesis of the dorsal pancreas features as shown by positron emission tomography/CT, ERCP, or MRCP are necessary to reveal the major and accessory duct systems. 10 Differential diagnoses of agenesis of the dorsal pancreas include pancreas divisum and pseudo-agenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Kabnurkar et al. 9 recently reported that features of agenesis of the dorsal pancreas features as shown by positron emission tomography/CT, ERCP, or MRCP are necessary to reveal the major and accessory duct systems. 10 Differential diagnoses of agenesis of the dorsal pancreas include pancreas divisum and pseudo-agenesis.…”
Section: Discussionmentioning
confidence: 99%